Rising incidence of hepatitis B‐related hepatocellular carcinoma in South Australia: 1996–2010. Issue 8 (August 2016) - Chinnaratha, M. A.; Graham, C.; Fraser, R. J. L.; Woodman, R. J.; Wigg, A. J.
Abstract : Background: Chronic hepatitis B virus (HBV) infection is likely to be an important driver of increasing hepatocellular carcinoma (HCC) incidence in Australia. However, there is paucity of Australian data on HBV‐related HCC incidence or outcomes. Aims: To determine the incidence rates and survival trends of HBV‐related HCC in South Australia (SA) over 15 years. Methods: A population‐based cohort study was performed in HBV patients notified to the SA Communicable Disease Control Branch between 1996 and 2010. The dataset was probabilistically linked with the SA Cancer Registry and death registry. Incidence rate trends and survival were determined for three 5‐year time periods (1996–2000, 2001–2006 and 2006–2010). Results: Forty‐seven of 3881 notifications with HBV were linked to a HCC record (median (interquartile range) age at diagnosis: 58.9 (13.4) years, 83% males, 8.5% born in Australia, 62% diagnosed between 51–69 years). The overall crude HCC incidence was 111.3/100 000 person‐years with an age‐standardised HCC incidence of 189.1/100 000 person‐years, the rate for men was higher than for women: 241.7 versus 88.6/100 000 person‐years. The age‐standardised HCC incidence increased over time with an annual percentage increase of 20.8% (95% CI: 10.06–32.54, P = 0.001). Median survival following HCC diagnosis was 12.5 months (95% CI: 3.6–21.4), with a trend towards longer survival during the 2006–2010 time period (21.8 months) compared to the previous two time periods (9.2 and 10.2 months, P = 0.056). Conclusion: Both crude and age‐standardised incidences of HBV‐related HCC increased between 1996 and 2010 in SA. There was a trend to longer survival in the latter time‐period.